Managing Employee Retention Concerns: Evidence from U.S. Census Data - Labro, Eva; Omartian, James D. (The Accounting Review, 2025)
ABSTRACT Using Census microdata on 28,000 manufacturing plants, we examine how firms manage employee retention concerns. In response to reductions in the local unemployment rate, plants take additional steps beyond increasing compensation. First, plants adjust bonus architecture to ensure bonuses can be paid. Second, plants offer more agency to employees by deploying high-involvement work practices that generate longer-term commitment. Third, plants pull these retention levers less when they have high availability and use of data as this reduces the adverse effects of employee turnover on organizational knowledge. These results are robust to using the fracking revolution as a shock increasing firms’ retention concerns. Additionally, we observe that although compensation increases tend to spill over to other plants within the same firm—aligning with theories of inequity aversion—adjustments to bonus architecture and the provision of employee agency do not, suggesting these may be more cost-effective strategies for multiplant firms. JEL Classifications: J63; M51; M54.